A microchip integrating cell array positioning with in situ single-cell impedance measurement. Issue 19 (7th October 2015) - Guo, Xiaoliang; Zhu, Rong; Zong, Xianli
<x xml:space="preserve">Abstract</x> A micro-chip integrating cell positioning with in situ, real-time and long-time impedance measurement on a single cell using nano-modified measuring electrodes.